Brazilian spotted fever in dogs - Fortes, Fernanda Silva; Dutra, Leonardo Hermes; Biondo, Alexander Welker; Molento, Marcelo Beltrão (Semina: Ciências Agrárias, 2011)
Brazilian spotted fever (BSF) is caused by bacteria Rickettsia rickettsii, highly pathogenic for humans and dogs, and has the Amblyomma cajennense tick as its main vector. Dogs maybe have a significantly participation on the BSF epidemiology, particularly in urban areas, due to the close contact with human beings. Several serologic studies in dogs from different Brazilian regions have indicated a previous contact of these animals with the R. rickettsii, and they are even considered as sentinels for the bacteria distribution. Although dogs are susceptible to R. rickettsii infection, the clinical disease in dogs has been very recently described in Brazil. Common signs of infection may include fever, depression, anorexia, ocular lesions, hemorrhagic petechiaes, anemia and thrombocytopenia, which also may appear in other diseases, such as the canine monocytic ehrlichiosis, considered the most common disease in dogs transmitted by ticks in Brazil. Thus, BSF clinical diagnosis in dogs may be confused by other diseases, causing its sub-notification. The aim of the present review article on BSF in dogs was to describe epidemiologic, clinical and diagnosis aspects, including also the main alternatives for its treatment and control.